(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
Injury crimes have different forms of completion and are characterized by various elements, for example, race, color, ethnicity, religion, geographic space and others. Language has a direct relationship with these elements, since it is part of the geographic space where it is spoken, the culture, and the ethnicity of its speaker. Considering this interaction, this article addresses a relationship between Criminal Law and Ecosystem Discourse Analysis, aiming to recognize linguistic insult as a qualifier for language crimes.